Persistence of Mast Cell-Positive Synovitis in Early Rheumatoid Arthritis Following Treatment With Conventional Synthetic Disease Modifying Anti-Rheumatic Drugs - Rivellese, Felice; Rossi, Francesca W.; Giorli, Giovanni; Napolitano, Filomena; de Paulis, Amato; Pitzalis, Costantino (Frontiers in Pharmacology, 2020)
Mast cells (MCs) are immune cells infiltrating the synovial membrane and implicated in the pathogenesis of Rheumatoid Arthritis (RA). Their infiltration in the synovia of early RA patients has been shown to be associated with systemic inflammation, disease activity and autoantibody positivity. Here, we analysed their presence in matched synovial samples obtained by ultrasound-guided synovial biopsies pre- and post-treatment with conventional synthetic Disease Modifying Anti-Rheumatic Drugs (csDMARDs) (n=20). Upon IHC staining, patients were classified as MC+ve/-ve based on the presence/absence of CD117+ synovial MCs. At baseline, MC+ve patients had significantly higher synovial inflammation, inflammatory markers, disease activity and a higher prevalence of lympho-myeloid aggregates. Synovial biopsies after 6 months of treatment with csDMARDs showed a significant reduction of synovitis scores, but only a partial reduction of MC numbers. Accordingly, 45% of patients (9/20) were MC+ve after treatment, in association with significantly higher degree of synovitis and higher proportion lympho-myeloid aggregates. Additionally, patients with MC+ve synovitis at 6 months had significantly higher disease activity and a lower rates of low disease activity. Overall, these data suggest that persistence of MC+ve synovitis is associated with lack of response to DMARDs. This study confirms the relevance of MCs as part of the inflammatory infiltrate in the synovia of RA patients, warranting further investigations to clarify their role in disease progression and response to treatment and their relevance as prognostic markers and potential therapeutic targets.